Regime of fluvial phosphorus constituted by sediment - Li, Huali; Zhou, Jianjun; Zhang, Man (Frontiers in Environmental Science, 2023)
Phosphorus (P) is a crucial macronutrient, and recently a venture agent of pollutant, in aquatic systems worldwide. Most of P circulates with sediment through rivers, and the relationship between P and sediment is the basis for understanding the biogeochemical processes in rivers. Although studies of fluvial P have been carried out at specific sites and for particular problems, the general regime by which sediment affects P recirculation still warrants attention. In this study, a series of water samples were collected from six different rivers in China whose sediment concentration and size distribution vary widely and their P properties were analyzed in the laboratory. From this analysis of field samples, a highly consistent comet shaped pattern of sediment effects on P is revealed, i.e., generally the range of the concentration of total P has a diverge-converge trend as the sediment concentration increases. It is further supported by examining the strictly composed samples from P adsorption experiments. Furthermore, case analyses were performed on the basis of the above relationships to illustrate the impact of sediment on P cycling in rivers. The results can infer the following: 1) There is a strong positive correlation between total P and sediment concentration, indicating that sediment is a crucial agent in the movement and fate of P. 2) The negative correlation between dissolved P and sediment concentration indicates a buffering effect of sediment, especially fine sediment, on dissolved P, interpreting the intricate phenomena of increased dissolved P concentration caused by sediment reduction. Hence, natural sediment has the prevailing advantage in moderating the water quality of rivers, which is directly relevant to mitigating the present pollution and eutrophication of waters. 3) River damming causes a P blockage tendency, altering the fluvial nourishment to contamination in the river.